Distinction between forensic evidence and dermatological findings. (July 2015) - Hammer, U.; Boy, D.; Rothaupt, D.; Büttner, A.
Abstract: The external examination after death requires knowledge in forensics/pathology, dermatology, as well as associated diseases and age-related alterations of the skin. This article highlights some findings with forensic evidence versus dermatological findings. The lectures in forensic medicine should be structured interdisciplinarily, especially to dermatology, internal medicine, surgery, pathology, and toxicology in order to train the overlapping skills required for external and internal postmortem examinations. Highlights: Differential diagnosis as a term mostly used concerning clinical medicine also should be used in forensic fields. The main goal of this article is the visualization of findings with forensic evidence versus dermatological findings. Lectures in forensic medicine should be structured interdisciplinary to train postmortem examination.